Geometrical analysis of the 3-D structure of the western Tauern Window (European Eastern Alps) - J. Rudmann; D. C. Tanner; M. Stipp; H. Pomella; C. Brandes (International Journal of Earth Sciences, 2025)
The Tauern Window (TW) in the European Eastern Alps is one of the most prominent tectonic windows on earth. Deeper structural levels of the orogenic wedge are almost completely exposed, which is why complex collisional deformation processes, including indenter tectonics, can be studied. Although the TW has been investigated over decades, its present-day, 3-D geometry is not completely deciphered. However, it provides insights into its Miocene deformation history, which is still debated. The latter was driven by indentation tectonics, which heavily shaped the structure of the TW, especially its western part. The aim of this study is to infer the Miocene deformation history from the present-day, 3-D structure of the upper crust of the western TW and to relate it to possible deeper crustal deformation processes. For the first time, we uncover the large-scale structure of the western TW, including two end-member models of the viscous Brenner normal fault by constructing a 3-D model using the software MOVE™. Our model reveals that the south-vergence of the large-scale antiforms increases in westerly direction and their cylindricity decreases in southern direction, thus, towards the front of the Dolomites indenter. Protruding middle and lower crust of the Dolomites indenter below the area of the TRANSALP seismic section could be responsible, also for the westward plunge of the entire western TW, which might have favoured the development of the Brenner normal fault. The Schöberspitzen antiform likely developed pre- or synkinematically to the westward plunge of the western TW, thus during the Miocene. Graphical abstract

Extracellular matrix 1 (ECM1) regulates the actin cytoskeletal architecture of aggressive breast cancer cells in part via S100A4 and Rho-family GTPases - P. Gómez-Contreras; J. M. Ramiro-Díaz; A. Sierra; C. Stipp; F. E. Domann; R. J. Weigel; G. Lal (Clinical & Experimental Metastasis, 2017)

Hematologic Values of Free-ranging Cebus cay and Cebus nigritus in Southern Brazil - Karina Keller Marques da Costa Flaiban; Kledir Anderson H. Spohr; Luciano de Souza Malanski; Walfrido Kühl Svoboda; Marcos M. Shiozawa; Carmen Lúcia S. Hilst; Lucas Moraes Aguiar; Gabriela Ludwig; Fernando C. Passos; Italmar Teodorico Navarro; Mara Regina Stipp Balarin; Júlio Augusto Naylor Lisbôa (International Journal of Primatology, 2008)

In vitro morphogenesis of Cucumis melo var. inodorus - Liliane C. Liborio Stipp; Beatriz M. Januzzi Mendes; Sonia M. D. Stefano Piedade; Adriana P. Martinelli Rodriguez (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)